A case report and review of literature: Tuberculous pericarditis with pericardial effusion as the only clinical manifestation - Wang, Shipeng; Wang, Jingyue; Liu, Junqian; Zhang, Zhiyu; He, Jiahuan; Wang, Yushi (Frontiers in Cardiovascular Medicine, 2022)
Tuberculosis is a main cause of pericardial disease in developing countries. However, in patients with atypical clinical presentation, it can lead to misdiagnosis, missed diagnosis, and delayed treatment. In this study, we report a case of a 61-year-old woman admitted to the cardiac intensive care unit with “weakness and loss of appetite” and a large pericardial effusion shown by echocardiography. After hospitalization, a pericardiocentesis was performed, and the pericardial fluid was hemorrhagic. However, the Xpert MTB/RIF and T-SPOT tests were negative, and repeated phlegm antacid smears and culture of pericardial fluid did not reveal antacid bacilli. The patient eventually underwent thoracoscopic pericardial biopsy, which revealed extensive inflammatory cells and significant granulomas. Combined with the fact that the patient’s pericardial effusion was exudate, the patient was considered to be suspected of tuberculous pericarditis (TBP) and given empirical anti-tuberculosis treatment the patient’s symptoms improved and the final diagnosis was TBP. In this case report, it is further shown that a negative laboratory test cannot exclude tuberculosis infection. In recurrent unexplained pericardial effusions, the pericardial biopsy is feasible. In countries with a high burden of tuberculosis, empirical antituberculosis therapy may be used to treat the pericardial effusion that excludes other possible factors.